Heterologous production of L-glutaminase through screening and isolation from locally isolated microbes - Ramli, Aizi Nor Mazila; Tajuddin, Saiful Nizam; Zamri, Normaiza; Abd Hamid, Hazrulrizawati (2018)
L-glutaminase present in living organisms namely human, animals, plants, and microorganisms. L-glutaminase has been identified having potential applications for several industries including pharmaceutical, food, and health care. Industrial sectors nowadays demand natural producing enzyme compared to artificial enzymes due to several safety issues. On top of that, L-glutaminase extracted from microorganisms has more advantages and benefits to fulfil demands from industries. Up until now, less research about bacteria production of Lglutaminase from Malaysia marine environments had been carried out. Hence, the objectives of this research study is to have an in-depth investigation on L-glutaminase production, optimization and characterization of partially-purified L-glutaminase from bacteria of Malaysia marine environment. In this study, the screening of bacteria-producing Lglutaminase had been implemented from three different Pahang Beaches known as Pantai Teluk Cempedak, Pantai Batu Hitam, and Pantai Balok. This was followed by biochemical characterizations and 16S rRNA gene sequencing to identify the identity of bacteria that showed positive results on L-glutaminase production. Additionally, production optimization, enzyme purification and characterization were carried out from the best L-glutaminase producer. The highest enzyme activity recorded was Kosakonia radicincitans with 0.103 U/ml followed by Shigella flexneri which has the enzyme activity of 0.100 U/ml. Furthermore, two isolates that had the highest enzyme activity were selected for optimization of process parameters through One Factor at A Time method. The parameters involved are temperature, pH, additional of organic and inorganic nitrogen sources, and additional of carbon sources. It was found out that K. radicincitans had the highest enzyme activity of 0.3542 U/ml at temperature 37°C, pH 7, additional of beef extract for organic nitrogen source, additional of ammonium chloride for inorganic nitrogen source, and additional of glucose for carbon source. L-glutaminase extracted from K. radicincitans was further partially purified and characterized. It had molecular weight of 70 kDA. L-glutaminase was most reactive and stable at temperature of 37ºC and pH 7. The information on production, optimization, and characterization of Lglutaminase are very important in order to understand its characteristics and suitability for industrial usage.